Comparison of blood lipid profile/thyroid function markers between unipolar and bipolar depressed patients and in depressed patients with anhedonia or suicidal thoughts - Meilei Su; Enze Li; Chong Tang; Yongzhi Zhao; Ruqing Liu; Keming Gao (BMC, 2019)
Abstract Background This study aimed to investigate the differences in the serum levels of glucose, lipid, and thyroid function markers between unipolar and bipolar depressed patients, as well as the effect of anhedonia and suicidal thoughts on the levels of these biochemical parameters. Methods A total of 287 unmedicated depressed patients from January 2016 to December 2017 were included in this study, including 92 bipolar depressions and 195 unipolar depressions. Anhedonia was determined using the item 32 of Symptom Checklist (SCL-90). Suicide ideation was assessed by item 15 of SCL-90. Results The bipolar group had significantly lower lipid levels (including triglycerides, cholesterol, low-density lipoprotein cholesterol [LDL], very low-density lipoprotein cholesterol [VLDL]) and insulin resistance index but higher levels of prolactin, low triiodothyronine (T3) and free T3 (FT3) as well as higher incidence of anhedonia as compared with the unipolar group. Depressed patients with anhedonia had significantly higher LDL level than those without anhedonia. Depressed patients with suicidal thoughts had cholesterol and high-density lipoprotein cholesterol (HDL) level. The above-mentioned differences were confirmed by logistic regression analysis. Receiver operating characteristic curve (ROC) analysis showed that the area under the ROC curve (AUC) ranged from 0.546 to 0.685. Conclusion Triglycerides, cholesterol, LDL, VLDL T3, FT3 levels were significantly different between unipolar and bipolar depressed patients, which might have the potential to be the markers for differential diagnosis. Patients with anhedonia had lower LDL level, while patients with suicidal thoughts had higher levels of cholesterol and HDL as compared with the corresponding control groups.